Changes in the clinicopathological characteristics and genetic alterations of follicular thyroid cancer. Issue 6 (December 2017) - Song, Young Shin; Lim, Jung Ah; Min, Hye Sook; Kim, Min Joo; Choi, Hoon Sung; Cho, Sun Wook; Moon, Jae Hoon; Yi, Ka Hee; Park, Do Joon; Cho, Bo Youn; Park, Young Joo
Abstract : Objective: Changes in the clinicopathological characteristics and genetic alterations of follicular thyroid cancer (FTC) over time have not been reported. Moreover, the prognostic effects of RAS and TERT promoter mutations in FTC have not been clearly elucidated. We investigated changes in the clinicopathological characteristics of patients with FTC over four decades, as well as the clinical significance of genetic mutations of FTC. Design and methods: This retrospective study included 690 patients with FTC who underwent thyroidectomy between 1973 and 2015 at the Seoul National University Hospital. In 134 samples, genetic tests for N/H/KRAS and TERT promoter mutations and PAX8/PPARγ rearrangement were performed. Results: The age at diagnosis has increased ( P  < 0.001) in recent decades and extrathyroidal extension of the tumor has become less common ( P  = 0.033). Other clinicopathological characteristics and prognosis of FTC have not significantly changed. The prevalence of RAS mutations decreased ( P  = 0.042) over time, whereas that of TERT promoter mutations remained stable. RAS mutations were associated with distant metastasis and persistent disease, and TERT promoter mutations were associated with distant metastasis, advanced TNM stage, recurrence and disease-specific mortality. FTC patients with coexistent RAS and TERT promoter mutations showed a higher recurrence risk than those with only one mutation. Conclusions: The age at diagnosis of FTC and the frequency of extrathyroidal extension have changed over four decades. Moreover, the prevalence of RAS mutations decreased. RAS and TERT promoter mutations may be associated with poor clinical outcomes in FTC, especially when the two mutations coexist.